A systems approach to achieving CarerNet-an integrated and intelligent telecare system. - Williams, G. (IEEE Transactions on information technology in biomedicine)
The system requirements for an integrated telecare system are presented by using a modification of the CORE methodology. The resulting system model uses viewpoint analysis to establish the needs and requirements of both the client and the care providers within a system context and discusses the implications for a user-centered, technology-based solution referred to as CarerNet. The implementation of CarerNet is considered in terms of the enabling technologies required within the local environment of the client and identifies the monitoring, networking requirements, and system intelligence necessary to the provision of a comprehensive telecare service. A hypothetical case study based on patient aftercare following discharge from the hospital is presented to illustrate the points discussed.